Independence of Madurese women’s healthy lifestyle with Ajhemo - Sri Ratnawati,; Ali, Moch; Wirata, Gede (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2020)
Ajhemo (herbal drink) is part of the routine of Madurese women in maintaining their health and fitness. This habit is the effect of biological traits of women who experience menstruation and childbirth. Women are required to drink herbal medicine by following the cycle. In addition, cultural factors encourage women to do ajhemo to meet the demands of their husbands. In connection with this, many Madurese women choose the type of jhemo (herbal medicine) related to the health of sexual organs. Nowadays ajhemo is a healthy way of life that Madurese women continue to do as the art of body exercise that includes cleanliness, beauty and health. Ajhemo for women has become a healthy way of life that has continued for generations. Ajhemo is a daily need believed to increase fitness to arouse sexual desire and aesthetics.